'Charmer boys' and 'cream girls': how primary school children construct themselves as heterosexual subjects through football. Issue 1 (2nd January 2018) - Mayeza, Emmanuel
ABSTRACT: South African research on young children's constructions of social identities illuminates the significance of play in the construction of gender identities. However, what remains largely understudied are the children's construction of sexualities through play. The dominant discourse of 'childhood innocence' obscures the variegated understandings of the meanings children attach to sexualities. This paper will explore how some South African boys and girls aged 9–10 years construct themselves as active heterosexual subjects through football talk and play during break-time at school. The paper will demonstrate how the school playground is constructed by the 'charmer boys' as a 'football space' where they use football performance to impress and charm the 'cream girls' who are relegated to the margins as spectators of the football games. However, the paper will also argue that gender power relations are complex and that the position of the 'creamers' is infused with power as reflected in the role that they play as assessors of the boys' performance.